Implementation Blessing Friday Movement Policy as Development of Social Capital - Madison; Irwan; Elvawati (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
MTSN 2 Solok School has carry out policy in the form of a Friday Movement program blessing. Research purposes This is analyze implementation Friday Movement policy blessing as development of the social model at MTS N 2 Solok. Study This use Lesser theory for analyze implementation Friday Movement policy blessing in development of social capital. Study This use approach qualitative with type study descriptive. The data collection method begins with observation, interview in depth and study document. Study analyzed with use Milles and Huberman analysis. Research result This showing that Friday Movement blessing can increase the strength of social capital on the part school with participant educate in aspect concern. Forms of social capital that are built is strengthen it solidarity fellow party school and its formation behavior togetherness for inhabitant school. This matter bring up attitude For each other help between One with others.